Staffing as a topical issue of the modern fitness industry - Myroslav Dutchak; Liubov Chekhovska (Kharkiv State Academy of Physical Culture, 2018)
The article substantiates the problem of staffing the fitness industry of Ukraine. Purpose: to study the current state of the problem of staffing in the system of health fitness in Ukraine. Material & Methods: theoretical analysis and synthesis of scientific literature, sources and information of the world Internet, comparison and comparison method, system analysis, organizational analysis, expert evaluation. Results: in recent years have increased the attention of scientists to personnel issues in the field of physical culture and sports, in particular - fitness. The strengthening of the social significance of the professional activities of fitness industry professionals is due to new socio-economic changes, the development of our state in accordance with the new market conditions. The processes of transformation, globalization and integration that are currently taking place in the system of health fitness in Ukraine require the improvement of its staffing. The necessity of providing the labor market with competitive specialists has been proved, since in the professional environment there is a shortage of qualified fitness personnel and a mismatch of competencies in a large part of the existing personnel with modern challenges. Conclusions: the need for scientific substantiation of the concept of staffing in the system of health fitness in Ukraine has been actualized in order to overcome the revealed contradictions between existing practice and the requirements of modernity.